1997
DOI: 10.1016/s0370-2693(97)00605-9
|View full text |Cite
|
Sign up to set email alerts
|

N = 4 super NLS-mKdV hierarchies

Abstract: N = 2 extension of affine algebra sl(2) ⊕ u(1) possesses a hidden global N = 4 supersymmetry and provides a second hamiltonian structure for a new N = 4 supersymmetric integrable hierarchy defined on N = 2 affine supercurrents. This system is an N = 4 extension of at once two hierarchies, N = 2 NLS and N = 2 mKdV ones. It is related to N = 4 KdV hierarchy via a generalized Sugawara-Feigin-Fuks construction which relates N = 2 sl(2) ⊕ u(1) algebra to "small" N = 4 SCA. We also find the underlying affine hierarc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 19 publications
(59 reference statements)
2
38
0
Order By: Relevance
“…Finally, noting that v = D −1 0 , Du x = 1 , combination of the equations (37), (38), and (39) gives Lax pair (36).…”
Section: Bilinear Bäcklund Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, noting that v = D −1 0 , Du x = 1 , combination of the equations (37), (38), and (39) gives Lax pair (36).…”
Section: Bilinear Bäcklund Transformationmentioning
confidence: 99%
“…In recent years, supersymmetry has been a subject of considerable interest in both physics and mathematics. It has been shown that these supersymmetric integrable systems possess bi-Hamiltonian structure, Painlevé property, infinite many symmetries, Darboux transformation, Bäcklund transformation, super soliton solutions [26][27][28][29][30][31][32][33][34][35][36][37]. However, application of Hirota's bilinear method to supersymmetric equations has been launched only in recent years [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In the unfrustrated case, the linear spin-wave theory (LSWT) has already been successfully applied in a series of recent works [4]. The second-order 1/S series for a number of quantities were shown [10] to reproduce with a high precision the density matrix renormalization group (DMRG) results. Thus, we can expect that at least in the weakly frustrated region the spin-wave theory (SWT) gives a realistic picture of the low-energy physics of the system.…”
Section: Spin-wave Analysismentioning
confidence: 99%
“…Superization of Polyakov's action and Nambu's action leads to interesting supersymmetric integrable systems (see, e.g., Ref. 13,16,21,18, and refs. therein), super versions of minimal surfaces and constant curvature surfaces, but we can not describe critical dimensions in these terms.…”
Section: Introductionmentioning
confidence: 99%